Mind Mapping Strategy in Improving Students’ Writing Skill in Politeknik Unggul LP3M Medan - Hermansyah Hermansyah (Universitas Syiah Kuala, 2023)
Abstract: The research objectives are to find out the differences in writing skills between students who write essays with mind mapping, and the conventional and the effectiveness of mind mapping in improving student’s writing skills in the 2nd semester of the Accounting study program at Politeknik Unggul LP3M. The research applied Pretest-Posttest Control Group Design. Two out of three classes of the population were selected as the research sample randomly namely class AK-AP2A/21 as the control group, and class AK-AP2B/21 as the experimental group. The research instrument used was an essay writing assessment sheet. The validity of the research instrument was content validity and the reliability was calculated by using Cronbach’s Alpha internal consistency technique. The research results show a significant difference in writing essays between students in the experimental group and the control group. The t-test calculation indicates it for the independent sample in the form of a t-count score that is greater than the t-table score (tc=5.506 tt= 1.990) at a 5% level of significance with 70 df. The other research result shows writing essays using mind mapping is more effective than the conventional one. It is indicated by the results of the t-test for paired samples show that the t-score (tc) is 14,636 with 35 df. The t-count score is consulted with the t-table value at a 5% significance level with 35 df. The t-table score (tt) at a 5% significance level with 35 df is 2.031. It shows that the t-count score is greater than the t-table score (tc =14,636 tt = 2,031)